Evaluasi Usability Aplikasi Mobile menggunakan Usability Testing dan System Usability Scale (SUS) (Studi Kasus: SOCO, Althea dan Sephora) - Raisadya Hemas Pawestri; Hanifah Muslimah Az-Zahra; Alfi Nur Rusydi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
For a decade, Indonesian people began to accept the presence of e-commerce as a medium of buying and selling online. The existence of e-commerce indulges buyers with a wider variety of products because it expands a wider market compared to products sold in physical stores. However, the phenomenon of the spread of e-commerce is not in line with the results of a survey conducted by the Indonesian Internet Service Providers Association (APJII) which states that there are still 58.8% of total internet users in Indonesia who have never made online purchases and involve 12.2% of users who have never done an online shopping transaction because they cannot use the application yet. There are still many mobile applications on the market that are difficult to use and learn because e-commerce usually has a very complex interface with various layers of menus. In fact, the usability aspect is the key to the success of applications and the conditions of user acceptance of mobile applications. Evaluation is carried out on applications that sell beauty products namely SOCO, Sephora, and Althea. Evaluation of usability is done using evaluation task scenarios, SUS questionnaires, and interviews. The final results of the evaluation of the Althea application are superior to all parameters of the task testing scenario. The final score of the SUS questionnaire in the Althea application was also the highest compared to the SOCO and Sephora applications. The results of this evaluation are also in line with the results of interview respondents who gave positive responses to the Althea application because it has the simplest design.